ASSESSMENT MECHANISM OF THE STRATEGIC EFFICIENCY OF PROJECTS ON THE СREATION OF HIGHTECH PRODUCTS IN THE AVIATION INDUSTRY - A. Bondarenko (Вестник университета, 2019)
Based on the results of the analysis of the activity of enterprises of different sectors of the aviation industry, the factors, influencing their effectiveness, have been identified, grouped and highlighted. In this article more than five problem zones of the aviation industry of the Russian Federation have been enumerated. The assessment mechanism of the strategic efficiency of projects on the creation of high-tech products in the aviation industry has been schematically presented. The central block of the mechanism has been described in detail – the method of determination of projects strategic effectiveness on the creation of high-tech products in the aviation industry.